Beyond Awareness: The Impact of Integrated Media and Interpersonal Communication on Maternal Handwashing Behavior in Indonesia - Fadjriah, Rasyika Nurul (Yayasan Sinergi Kawula Muda, 2025)
Inadequate hand hygiene continues to pose a major public health threat, particularly in low- and middle-income countries such as Indonesia. This study investigates the influence of combined media and interpersonal communication (IPC) campaigns on maternal handwashing behavior. Utilizing a qualitative synthesis of empirical data from Hanson et al. (2020) and Hirai et al. (2016), This study applied thematic and conceptual analysis grounded in Social Cognitive Theory and the Health Belief Model. The methodology draws on secondary data and literature-based thematic patterns to explore behavior change dynamics. Findings indicate that media alone increases awareness but often fails to lead to sustained behavior change. In contrast, IPC enhances message retention, fosters trust, and enables culturally relevant reinforcement of health behaviors. When used in tandem, media and IPC significantly improve both knowledge and handwashing practices among mothers. Emotional and social motivators, such as concern for child safety and peer influence, further drive behavioral adoption. The results suggest that integrated health campaigns that combine media outreach with interpersonal reinforcement are more effective in promoting hygiene compliance. These insights offer practical guidance for designing community-centered health interventions, particularly in LMIC contexts. The study emphasizes the need for multi-modal, culturally grounded health communication strategies to address hygiene-related challenges.